Dispersive solid phase extraction of ginkgolide B from real samples using 3D reduced oxide graphene aerogel based molecularly imprinted polymers. (15th July 2022) - Yang, Chengying; Li, Honghong; Wu, Zeyu; Huang, Xusheng; Zhou, An; Hui, Ailing; Liu, Rui; Zhang, Wencheng
Abstract: In this article, novel molecularly imprinted polymers based on 3D reduced graphene oxide aerogel (3D RGO‐GBMIPs) were successfully fabricated and applied as adsorbents for dispersed solid‐phase extraction (DSPE) of ginkgolide B (GB). After being prepared by surface molecular imprinted technology, 3D RGO‐GBMIPs were successively characterized by fourier transform infrared spectroscopy, thermogravimetric analysis, Raman spectroscopy, and scanning electron microscope. The results of adsorption experiments revealed that 3D RGO‐GBMIPs presented highly selective recognition properties and well reusability. The main variables influencing DSPE efficiency, including extraction solvent, 3D RGO‐GBMIPs dosage, category, and volume of eluent, as well as elution time were investigated. The DSPE results showed that 3D RGO‐GBMIPs had an obvious effect on the improvement of GB purity in ginkgo biloba extract, with a satisfactory recovery rate and yield. Therefore, 3D RGO‐GBMIPs are expected to be applied for the enrichment of GB from complex matrices.